OP9 Feeder Cells Are Superior to M2-10B4 Cells for the Generation of Mature and Functional Natural Killer Cells from Umbilical Cord Hematopoietic Progenitors - Herrera, Lara; Salcedo, Juan Manuel; Santos, Silvia; Vesga, Miguel Ángel; Borrego, Francisco; Eguizabal, Cristina (Frontiers in Immunology, 2017)
Adoptive natural killer (NK) cell therapy relies on the acquisition of large numbers of mature and functional NK cells. An option for future immunotherapy treatments is to use large amounts of NK cells derived and differentiated from umbilical cord blood (UCB) CD34+ hematopoietic stem cells (HSC), mainly because UCB is one of the most accessible HSC sources. In our study we compared the potential of two stromal cell lines, OP9 and M2-10B4, for in vitro generation of mature and functional CD56+ NK cells from UCB CD34+ HSC. We generated higher number of CD56+ NK cells in the presence of the OP9 cell line than when they were generated in the presence of M2-10B4 cells. Furthermore, higher frequency of CD56+ NK cells was achieved earlier when cultures were performed with the OP9 cells than with the M2-10B4 cells. Additionally, we studied in detail the maturation stages of CD56+ NK cells during the in vitro differentiation process. Our data show that by using both stromal cell lines, CD34+ HSC in vitro differentiated into the terminal stages 4-5 of maturation resembled the in vivo differentiation pattern of human NK cells. Higher frequencies of more mature NK cells were reached earlier by using OP9 cell line than M2-10B4 cells. Alternatively, we observed that our in vitro NK cells expressed similar levels of granzyme B and perforin and there were no significant differences between cultures performed in the presence of OP9 cell line or M2-10B4 cell line. Likewise, degranulation and cytotoxic activity against K562 target cells were very similar in both culture conditions. The results presented here provide an optimal strategy to generate high numbers of mature and functional NK cells in vitro, and point towards the use of the OP9 stromal cell line to accelerate the culture procedure to obtain them. Furthermore, this method could establish the basis for the generation of mature NK cells ready for cancer immunotherapy.